Evaluation of the Madrasah Head Supervision Program in Improving the Quality of Teacher Performance in MTsN 2 South Bengkulu - Puspasari, Nur; Utami, Yola Septia (Al-Khair Journal: Management Education, 2025)
Abstrac: The quality of teacher performance is still considered low because the principal’s supervision program has not been optimally implemented. This study aims to evaluate the madrasa principal’s supervision program in improving teacher performance quality at MTsN 2 South Bengkulu. It uses a descriptive qualitative method with the CIPP (Context, Input, Process, Product) evaluation model approach. Data were collected through observation, interviews, and documentation. The research results show that in the context of the madrasah principal’s supervision program, at the input level there are differences in teachers’ pedagogical competencies. At the process level, there are irregularities in the implementation of curriculum-based learning, as well as a lack of innovation in teaching methods. As for the output of the supervision program, teachers are able to carry out the learning process, develop RPS and RPP programs, and create innovations to improve education quality, supported by adequate tools to enhance teacher performance quality. Thus, the evaluation of the madrasah principal’s supervision program can improve the quality of teacher performance. Therefore, it is recommended that to improve teacher performance quality, the madrasah principal’s supervision at MTsN 2 South Bengkulu should be strengthened, even though several technical and cultural challenges still exist. This evaluation provides strategic recommendations for more sustainable and systematic supervision optimization in the future.Keywords: Evaluation, Principal’s Supervision Program, Teacher Performance Quality, MTsN 2 Bengkulu Selatan. Abstrak: Kualitas kinerja guru masih tergolong rendah, karena program supervise kepala madrasah belum optimal dilaksanakan. Penelitian ini bertujuan untuk mengevaluasi program supervisi kepala madrasah dalam meningkatkan kualitas kinerja guru di MTsN 2 Bengkulu Selatan. Menggunakan metode kualitatif deskriptif dengan pendekatan model evaluasi CIPP (Context, Input, Process, Product). Pengumpulan data melalui observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa conteks program supervise kepala madrasah, pada tingkat input program terdapat perbedaan kompetensi pedagogik antar guru, tingkat proses pelaksanaan program terjadi ketidakteraturan dalam pelaksanaan pembelajaran berbasis kurikulum, serta kurangnya inovasi dalam metode mengajar, produk program supervisi kepala madrasah guru dapat melaksanakan proses pembelajaran, menyusun program RPS, RPP, membuat inovasi dalam meningkatkan mutu pendidikan, didukung dengan perangkat yang memadai dalam meningkatkan kualitas kinerja guru. Dengan demikian evaluasi program supervise kepala madrasah dapat meningkatkan kualitas kinerja guru. Oleh karena itu, dapat disarankan. Untuk meningkatkan kualitas kinerja guru, maka tingkatkanlah supervise kepala madrasah di MTsN 2 Bengkulu Selatan meskipun masih terdapat beberapa hambatan teknis dan kultural. Evaluasi ini memberikan rekomendasi strategis untuk optimalisasi supervisi yang lebih berkelanjutan dan sistematis di masa depan.Kata kunci: Evaluasi, Program Supervisi Kepala Madrasah, Kualitas Kinerja Guru, MTsN 2 Bengkulu Selatan.